Design and Operation of Optical Fiber for Mass Measuring Instrument with Bending Power Loss Principle - Saktioto Saktioto; Wahyu Candra; Vepy Asyana; Romi Fadli Syahputra; Syamsudhuha Syamsudhuha; Dedi Irawan; Okfalisa Okfalisa; Haryana Hairi; Dadang Syarif Shihabudin Sahid (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
Utilization fiber optics macro-bending will be useful for non-destructive applications, such as a mass measurement device. This research, therefore, analyzes the fiber optic power loss due to macro bending by mass loading and explores its possible application as an instrument of mass scale. A single-mode fiber (SMF) with a core diameter of 8.2μm and laser with a wavelength of 1310 nm and 1550 nm are used in this  work. Moreover, an optical power meter with a sensitivity of 0.01dBm is applied as the detector while power loss is determined using nine bending cylinders that can produce eighteen bends with a roundtrip system. It is  obtaineda correlation coefficient R2of 0.9910 and 0.9959 corresponding to a sigmoid of 4 parameters for two-wavelength sources of 1310nm and 1550nm, respectively. The results showed mass suppression can produce a power loss with a relatively small error of 19.60%, 11.23%, 0.20%, 3.74%, and 9.36% for mass 300g, 600g, 100 g, 1400g, and 1800g, respectively